Vitamin D Deficiency and Autism Spectrum Disorder - Siracusano, Martina; Riccioni, Assia; Abate, Roberta; Benvenuto, Arianna; Curatolo, Paolo; Mazzone, Luigi (Current Pharmaceutical Design, 2020)
Vitamin D is a neurosteroid hormone crucially involved in neurodevelopment. Neural cell proliferation, neurotransmission, oxidative stress and immune function represent the main mechanisms mediated by vitamin D in the Central Nervous System. Therefore, its deficiency during pregnancy and early childhood may significantly impact on a developing brain, leading to possible adverse neuropsychological outcomes including Autism Spectrum Disorder (ASD). Significant vitamin D deficiency is described within children affected by ASD and in pregnant mothers whose offspring will later develop ASD, suggesting a possible role of the hormone as a contributing risk factor in the etiopathogenesis of ASD. We reviewed the actual literature on the potential contributing role of prenatal and early postnatal vitamin D deficiency in ASD etiopathogenesis, at both genetic and environmental levels, and the possible effect of vitamin D supplementation in autistic children. Conflicting but promising results emerged on the topic. Further Randomized Controlled Trials studies carried out during pregnancy and early infancy are necessary for better understanding the possible contribution of vitamin D deficiency in the etiopathogenesis of autism and the potential efficacy of the hormone supplementation in the improvement of ASD core symptoms.
Keywords: Vitamin D